Effects of Staggered Array of Cubical Obstacles on Near- Ground Wind Environment and Air Quality - Muhammad Yazid, Muhammad Noor Afiq Witri; Badar Sharif, Asyraf Sharif; Che Sidik, Nor Azwadi; Hanipah, M. H.; Mohd Zawawi, Fazila; Abidin, Ummikalsom (Penerbit Akademia Baru, 2019)
Deterioration of natural ventilation in outdoor environments due to rapid urbanisation has raised the issues pertaining to pedestrians’ thermal comforts and pollutant exposures. There are substantial interests in the recent years to get an insight on how deficient these situations are and later propose the appropriate urban layout for optimum wind ventilation in a dense urban area. The objective of this paper is to numerically study the effects of urban layouts (i.e., staggered arrangements and cubes’ densities) on wind ventilation and air quality near the ground subjected to one wind direction; perpendicular to the disposition direction. Computational fluid dynamics simulations were carried out by the use of standard k−ε turbulence model and found to be in fair agreement against the experimental data. Our result showed that loosely packed cubes exhibited lower pollutant concentration and higher wind speed near the ground compared to medium and densely packed cubes. Air quality was improved in closely packed cubes with staggered layout but did not show any improvement in medium and loosely packed cubes with staggered layout. Adversely, disposition of cubes exhibited lower wind speed compared to regular cubes for all street gap sizes. This paper also illustrates a practical strategy in optimising building layouts for wind flow enhancement and air quality improvement in an idealised urban area.